ACCOUNTING INNOVATION AND THE PSYCHOLOGY OF CHANGE. - Jones, Gardner M. (The Accounting Review, 1962)
The accounting professionals are quite preoccupied with "The New," and much of its vitality stems from its pursuit of "The New." Society seems to equate newness with progress, either rightly or wrongly. For one thing, there have been some pretty important changes in accounting technique or emphasis or methodology, arising out of developments in political economy, in physical technology, and in the organization of commerce. In political economy proposed methods of getting economic growth have their accounting implications. Federal tax policy and federal monetary policy are important agents or retardants in economic growth, and important determinants of changes in the accountant's task. To parallel these continuing changes in the practice of accounting, there are some necessities and some opportunities for change in educational methodology. When an accounting teacher begins to survey these areas in which innovation and/or change has taken place, he finds himself right in the middle of a complex in which everything seems to be shifting one way or another. This article attempts to explore the patterns in which people respond to change in their work situations, the ideas going in a man's mind-unknown even to himself, that causes him to react in a particular way to impending changes and accounting people's reaction, when someone else's new idea begins to affect them.